Interfaith Marriage and Its Implications for Children's Education in Multicultural Families - Firman Suryadi; Rina Puspita (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2023)
Interfaith marriages in Indonesia reflect the cultural and religious diversity of society. This research aims to understand the implications of interfaith marriages on children's education in multicultural families. Using a qualitative approach with a case study design, data was collected through in-depth interviews with interfaith couples, their children, educational practitioners, and policy makers in big cities such as Jakarta, Surabaya, and Medan. Findings show that interfaith families face challenges such as identity confusion and social anxiety in children due to social and community pressures. However, some children are able to combine religious values harmoniously, developing a more inclusive identity. Synergy between local communities and educational institutions is needed to support the education of children from multicultural families. This research provides a basis for policy makers and educational practitioners in formulating inclusive adaptive policies.